Optimasi Penjadwalan Kuliah Pengganti Menggunakan Algoritme Genetika - Holiyanda Husada; Imam Cholissodin; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Rescheduling is an option that can be chosen when lecturers are unable to attend on a schedule that has been determined by the academic or when there is a day off. This makes the lecturer need a rescheduling system to find another schedule quickly and appropriately to fulfill his duties as a lecturer. In this study use genetic algorithm for rescheduling based on lecturer schedule, student schedule, available room, course, and available time. The solution quality is measured using the fitness function. Based on the testing results that have obtained the optimal fitness value is 0.667. Result of Solution without clashed schedules but soft-constraint violated. The parameters with the highest fitness value from 10 experiments obtained the number of generation 30, population size 50, crossover rate 0.7 and mutation rate 0.3. The result is the optimal schedule available where the lecturers and most students of the class are reliable.